Cognitive Structure of Randomness - G. I. Berestnev (Научный диалог, 2021)
The cognitive structure of randomness, which is of research interest for modern cognitive linguistics is considered. It has the explanatory property — an explanation of the deep mechanisms of phenomena that allow meaningful interpretation. The goal, first outlined in linguistics, the identification of deep cognitive characteristics in the structure of thought about randomness in the Russian and Indo-European linguistic mentality with the involvement of typological data is being realized. The methodological basis of the research was made up of a complex of analytical techniques that make it possible to reconstruct the deep content structures of the human cognitive sphere on the basis of the surface semantic data of the language. The analysis of the motivation of words with the semantics of randomness in related and unrelated languages made it possible to establish that the revealed cognitive structure of randomness is not strictly universal and, in some aspects, turns out to be culturally conditioned. It is noted that the cognitive principle of thinking about randomness is complex, but diffuse in nature. It points to the explanatory power of modern linguistics, which is open to entering broad interdisciplinary spheres. It is concluded that the results of this study are of interdisciplinary significance and are relevant for modern fundamental sciences.